The Influence of Lifestyle, Income, and Financial Literacy on Religiosity and Consumptive Behavior Among Generation Z - Resky, Sry Wala Resky; Wahab, Abdul; Muin, Rahmawati (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
This study aims to analyze the direct and indirect effects of Lifestyle, Income, and Financial Literacy on Religiosity and Consumptive Behavior of Generation Z Shopee Pay Later users among Muslim students in Makassar City. The research employs a quantitative method with a descriptive approach, utilizing primary data from 120 respondents through a questionnaire. Analysis is conducted using the Structural Equation Model (SEM). The results indicate that Lifestyle and Income have a significant positive effect on Religiosity, while Financial Literacy has a negative but insignificant effect. Lifestyle and Financial Literacy positively influence Consumptive Behavior, whereas Income has a negative effect. Additionally, Religiosity positively affects Consumptive Behavior. The study highlights the importance of wise financial management for Muslim students to become more financially independent and to control their lifestyle in accordance with Sharia principles.